IN SILICO STUDIES ON DIACYL DERIVATIVES OF PHLOROGLUCINOL TO ENHANCE PHARMACODYNAMIC AND PHARMACOKINETIC PROFILES OF 2,4,6-TRIHYDROXY-3-GERANYL-ACETOPHENONE - CHIONG, SHEAU WEI; NG, CHEAN HUI; SHAARI, KHOZIRAH (International Journal of Applied Pharmaceutics, 2021)
Objective: The purpose of this study was to evaluate the LOX inhibitory activity, and predict the drug likeness properties of designed diacyl derivatives of phloroglucinol, using in silico method. Methods: The designed derivatives were subjected to molecular docking using AUTODOCK while the receptor used in this study was built from SWISS MODEL. Drug likeness properties of the derivatives were calculated by online programs i.e. MOLINSPIRATION and PreADMET. Results: Molecular docking study revealed that designed tHGA derivative with four-carbon chain length exhibited the best binding affinity with the docking scores of -7.26kcal/mol. Three types of binding interactions were observed between the derivatives and the receptor site i.e H-bonding, hydrophobic and Van der Waals interactions. The important amino acid residues involved in H-bonding were Gln495 and Gln697, while other amino acid residues, such as Leu754 and Ile 553, were involved in the Van der Waals interaction. The designed tHGA derivatives were mainly stabilized through hydrophobic interactions with His499, His504, Ile538, Phe557 and Val750. In silico physicochemical calculations predicted that all the designed derivatives passed the Lipinski’s Rule of 5, and have good human intestinal absorption property (HIA>70%). Further, all the designed derivatives showed moderate central nervous system absorption (0.6<BBB<2.0), except for the derivative with a longer (5-Cs) chain length. Conclusion: The findings of the present study suggested that changing the acyl and geranyl side chains of the natural product molecule, tHGA, into two acyl bearing side chains, will improve its pharmacodynamic and pharmacokinetic profiles.